The Effect Of Health Education On Knowledge About Anemia In Pregnant Mother - Fitriani; A.Nurlaela Amin; Uswatun Khasanah (Jurnal Life Birth, 2020)
Anemia in pregnancy is one of the national problems because it reflects the value of the socio-economic welfare of the community and its influence is very large on the quality of human resources. The prevalence of anemia in the world is very high, especially in developing countries including in Indonesia, anemia is still four of the nutritional problems that have not been resolved, even becoming the main cause of maternal and neonatal mortality. As many as 40 percents of deaths in pregnant women are caused by anemia. Therefore, anemia requires serious attention from all parties involved in health care. The purpose of this study is to know the effect of health education on the level of knowledge about anemia in pregnant women in the working area of ​​the Borong Rappoa Puskesmas. This type of research is a quantitative study with a pre-experimental research design through the one-group pretest-posttest design method. The sampling technique uses the non-probability sampling technique that is consecutive so that it gets 44 respondents as respondents. The results of the study used the Wilcoxon test with a significance value of <0.05. The results obtained before being given health education, most pregnant women lack knowledge as many as 40 people (90.9%) of respondents, enough as many as 3 people (6.8%) of respondents, either there is 1 person (2.3%) of respondents and after giving health education, most of the pregnant women have good knowledge as many as 39 people (88.6%) of respondents, have enough knowledge of 5 people (11.4%) of respondents, and lack of knowledge of 0 (0%), so p values ​​= 0,000 <0, 05 which means there are differences in the proportions before and after the provision of health education about anemia in pregnancy.